Preparation of transition metal sulfide nanoparticles via hydrothermal route - Fei-Ling Pua,; Chin-Hua Chia,; Sarani Zakaria,; Tze-Khong Liew,; Mohd Ambar Yarmo,; Nay-Ming Huang, (Universiti Kebangsaan Malaysia, 2010)
Nano sized copper sulfide, iron sulfide and molybdenum sulfide were successfully synthesised via a simple hydrothermal method. Sodium thiosulfate pentahydrate (Na2S2O3¥5H2O) and hydroxylamine sulfate ((H3NO)2¥H2SO4) were used as the starting materials and reacted with the transition metal source at 200oC for 90 min. The products were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX) and Fourier transform infrared spectroscopy (FTIR). Spherical shape CuS and FeS2 nanoparticles with high crystallinity were successfully produced. The transmission electron micrographs revealed the well-dispersibility of the produced nanoparticles. Scanning electron micrograph showed the MoS2 nanoparticles possessed a spherical shape with sheet-like structure covering on the outer surface of the particles.